Development of an advanced nano-satellite VELOX-II solar energy system (concentrated photovoltaic) - Han, Henry (2014)
Space has always been one of the primary concerns for many systems, and a challenge faced by many in developing continuously smaller and yet higher efficient energy harvesting system. This thesis reports a new energy harvesting system designed for the nano-satellite developed by the Satellite Research Centre of Nanyang Technological University (NTU). Developing a small energy harvesting system for a nano-satellite is evitable since the allowable dimension is constrained. The mass is also another consideration as the cost of launching a satellite into space is dependent on the mass. Through saving the space and mass, additional payloads can be implemented in the satellite making efficient use of the system. This project aims to develop a highly dense energy harvesting system to advance the current Photovoltaic system used by the typical nano-satellite. The energy harvesting system can also potentially be implemented onto a high altitude balloon that both Google and Facebook are adventuring.